Clinical Effectiveness of Platelet-Rich Plasma for Long-Bone Delayed Union and Nonunion: A Systematic Review and Meta-Analysis - Li, Shang; Xing, Fei; Luo, Rong; Liu, Ming (Frontiers in Medicine, 2022)
Background: More recently, there was a series of clinical studies focusing on local administration of platelet-rich plasma (PRP) in long-bone fracture patients suffering from delayed union and nonunion. Therefore, we performed a systematic review to evaluate the effectiveness of PRP injection for treatment of patients with long-bone delayed union and nonunion Methods: Relevant clinical trials were selected by the main bibliographic databases, including Medline, PubMed, Embase, Web of Science, and the Cochrane library, to evaluate the effectiveness of PRP for long-bone fracture patients diagnosed with delayed union or nonunion by two reviewers independently. The main outcomes included healing rate, healing duration, pain relief, functional outcome, and complications. Results: Finally, thirteen studies including four hundred and fifty-nine participants met the selection criteria and were included in this systematic review. These articles included three randomized controlled studies, one prospective study, and nine retrospective studies. 146 out of 155 (94.19%) patients treated with PRP during operation, and 144 out of 183 (78.69%) patients treated with PRP injection alone, exhibited bone consolidation. The healing rate of the PRP group (85.80%) was higher than that of the control group (60.76%). The mean bony union time of patients treated and untreated with PRP, were respectively 4.64 and 5.15 months. Four papers reported that PRP was effective in pain relief of patient with delayed union and nonunion. Complications, including small subcutaneous hematoma, subcutaneous swelling, and postoperative infection, were also reported in enrolled studies. Conclusions: PRP is a promising alternative treatment for patients with long-bone delayed union and nonunion. PRP could successfully promote the healing rate and relieve the pain of patients with delayed union and nonunion. However, the long-term adverse side and functional outcome in application of PRP still need further large-scale trials and long-term follow-up.